CONSTITUTIONAL AND LEGAL PRINCIPLES SOCIAL ASSISTANCE ORGANIZATION: POLISH EXPERIENCE FOR UKRAINE - Matviichuk, Andrii; Ryzhenko, Іgor (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Aim: study of the correlation between constitutional and legal principles and practical organization of social assistance in the Republic of Poland. In this regard, the achievement of the following tasks is stated: 1) to determine the constitutional and legal framework for the social security regulation in Poland; 2) to find out the mechanisms of practical organization and provision of social assistance corresponding to these principles. Research methods: analytical method was used as well as the method of generalization in combination with systematic and integrated approach. Results: at the theoretical level, the study found that the constitutional principles and regulations relating to the social sphere in Poland are implemented by both institutions at the level of state and local government. It confirms Poland’s desire not only to declare itself, but to be a socially oriented state. A fundamental precondition for this state of affairs in the social sphere is an effective correlation between the constitutional and legal principles and the practice of social assistance in Poland. Discussion: for Ukraine, the issue of organizing and providing social assistance is especially important in the context of the undeclared war, which in fact has been going on for more than eight years in the east of our country. This situation justifies attention to the theory and practice of social assistance organization and provision. At the same time, a special analysis shows that at the theoretical level, enough material has been developed to understand such basic concepts as «social sphere», «social policy» and «social assistance». Instead, there is a need to develop practical mechanisms to fill these concepts with content that would give citizens a sense of social security.